Improvements in Design of Local Fluorescent Electronic Ballasts in Compliance With the Related Local and International Standards - Yaacob, Zulkefli (2001)
The fluorescent electronic ballast has been in the market for a long time but has not created any great impact in the illumination industry due to its high initial cost of investment compared to the conventional magnetic ballast. With the advancement in power electronics and utilization of power semiconductor which is available commercially today, it is now possible to implement almost every type of desired conversion of current, voltage or frequency and availability of electronic components with higher power ratings. Thus, it is now possible to manufacture an economically priced, light weight, lower watt-loss and high quality with maximum performance electronic ballast which is compatible with all types of fluorescent luminaries. This study is undertaken to improve the design of existing locally manufactured electronic ballasts. The study indicated that many of these commercial electronic ballasts only have partial or minimum compliance requirements or none at all to the related local and international standards, namely MS IEC 928, MS IEC 929 and EMC requirements as stipulated by SIRIM Berhad. From a survey on nine different ballast manufacturers, only seven manufacturers conducted two tests on MS IEC 928 and MS IEC 929 and only two manufacturers conducted a complete list of tests to ascertain whether their product comply with the related local and international standards. Since electronic ballast is listed as one of the electrical controlled items by the Department of Electricity and Gas Supply of Malaysia (DEGSM), it is crucial that the EMC test be imposed prior to ballast approval. A directive was issued by the Malaysian government on the 3rd of July 1998 to implement energy conservation and to promote the use of energy efficient equipment specifically on lighting luminaries and lighting control systems. DEGSM noted the limitations of fluorescent ballast watt-loss hence, this study is undertaken to meet the implementation of energy conservation regulations/act in the near future.